(untitled) (Altre Modernità, 2011)
Ralph Ellison’s allegorical journey in Invisible Man (1994) launched a new era in African-American culture and Black literacy for the entire world in 1952. In 1965, Ellison’s tragic, Diasporic hero appears to have experienced a reincarnation in the epic of Manchild in the Promised Land (1999) by Claude Brown. Currently, lingering in the caverns of Shadows of Your Black Memory (2007), past and present, Donato Ndongo’s tragic, Diasporic hero (of Equatorial Guinean heritage) prompts us to relive the course of colonialism and neocolonialism ‘of the mind’ in this…. the new millennium. This paper addresses the trilogy of resistance writing in Ellison’s Invisible Man, Brown’s Manchild in the Promised Land, and Ndongo’s Shadows of Your Black Memory. The experiences of the writers, political issues illustrated, and the impact upon the Black literary landscape (universal) will be explored.